Android Studio New Media Fundamentals Content Production of Digital Audio/Video, Illustration and 3D Animation - Jackson, Wallace (Apress : Imprint: Apress, 2015)
Android Studio Content Production Fundamentals title introducing the reader to the concepts and terminology behind digital imaging (raster/bitmap/GIMP), digital illustration (vector/SVG/Inkscape), and digital audio (editing/effects/Audacity) and covers how to develop and optimize these types of content for use in Android OS using Android Studio 5.3.1. What You Will Learn • What are the primary genres of new media content production • What new media assets Android Studio supports • What are the concepts behind new media content production • How to Install and use GIMP, Inkscape, and Audacity software • How to integrate that software with Android Studio, fast becoming the most popular IDE for Android apps design and development.